The Network of Pro-Inflammatory Factors CD147, DcR3, and IL33 in the Development of Kawasaki Disease - Qi Y (Dove Medical Press, 2021)
Yanqi Qi,* Jiawen Xu,* Zhe Lin,* Yijing Tao, Fenglei Zheng, Yujia Wang, Yameng Sun, Songling Fu, Wei Wang, Chunhong Xie, Yiying Zhang, Fangqi Gong Department of Cardiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, 310052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fangqi GongDepartment of Cardiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, No. 3333 Binsheng Road, Hangzhou, 310052, People’s Republic of ChinaTel/Fax +86-571-88873008Email gongfangqi@zju.edu.cnIntroduction: Kawasaki disease (KD) is an acute febrile systemic vasculitis, but the etiology remains unknown. We studied serum levels of CD147, DcR3, and IL33 in different stages of KD to explore the value of CD147, DcR3, and IL33 in the pathophysiology of KD.Methods: We measured serum levels of CD147, DcR3, and IL33 by enzyme-linked immunosorbent assay (ELISA) at different stages with 71 KD patients and 66 healthy control children. We apply for network tools GeneMANIA and Cytoscape APP to analyze the functions of these pro-inflammatory factors at the gene and protein level.Results: Serum levels of CD147, DcR3, and IL33 were significantly increased in KD patients before IVIG treatment. Serum levels of CD147, DcR3, and IL33 gradually decreased over time after the treatment of IVIG. Eight cases were IVIG non-responders, while nine KD patients got CALs, but they did not overlap. And there were no statistical differences between group IVIG responders and IVIG non-responders or between groups without CALs and with CALs. We explored the functions of CD147, DcR3, and IL33 from GeneMANIA and Cytoscape APP and found these third pro-inflammatory factors were coexpressed, physical interactions, genetic interactions with other KD-related factors.Conclusion: CD147, DcR3, and IL33 are involved in the pathophysiology of KD, which provides novel evidence for diagnosing and treating KD with their inhibitors.Keywords: Kawasaki disease, coronary artery lesions, CD147, DcR3, IL33, PI3K/AKT pathway